Dual pathogen valvular endocarditis in a case of severe aortic aneurysm - Meghna Yadav; Rohit Tewari; Tathagata Chatterjee (University of São Paulo, 2022)
Infective endocarditis (IE) is the heart valve or endocardium infection. We report a rare case of polymicrobial endocarditis, namely invasive Aspergillus spp and Acinetobacter baumannii, in a 36-year-old male with a medical history of degenerative disease of the aorta with abdominal aortic and ascending aortic aneurysms with a fulminant clinical course and fatal outcome. The treatment was challenging due to multiple comorbidities. The autopsy revealed dual pathogen endocarditis due to Acinetobacter baumannii sepsis and invasive Aspergillus spp mycosis. This report emphasizes that polymicrobial endocarditis (PE) is an infrequent finding with a poor prognosis requiring high clinical suspicion.